The Impact of the Ukraine War and Sanctions on Foreign Trade in Selected EU Countries - Gorący, Jarosław (Acta Universitatis Lodziensis. Folia Oeconomica, 2025)
The aim of the paper is to analyse the impact of the armed conflict in Ukraine and the economic sanctions imposed on Russia and Belarus on the structure and dynamics of foreign trade of Poland and selected European Union countries. Particular attention is paid to changes in exports and imports and their consequences for the economies of the analysed countries. The paper uses statistical data analysis from Eurostat databases and other international economic institutions. The study was conducted at the macroeconomic level using trade indicators and comparing data before and after the introduction of sanctions. The analysis is supplemented by case studies for key sectors such as energy, machinery and agriculture. The results indicate significant changes in the structure of trade, including the redistribution of trading partners and a decrease in exchange with countries covered by sanctions. The analysis also reveals differences in the economic effects for individual EU countries, resulting from their level of dependence on the Russian and Belarusian markets. In Poland, an increase in exchange with alternative partners was noted, which indicates the adaptation of the economy to new conditions.